Deletion mutagenesis using an 'M13 splint': the N-terminal structural domain of tyrosyl-tRNA synthetase (B. stearothermophilus) catalyses the formation of tyrosyl adenylate. - Waye, M M (1983)
The X-ray crystallographic structure of tyrosyl-tRNA synthetase (TyrTS) comprises only the N-terminal 320 amino acids of the molecule as the C-terminal 99 amino acids are poorly ordered in the crystal. A new technique, employing a single-stranded M13 splint, has been used to direct a deletion in the cloned gene of TyrTS so as to remove the disordered C-terminal region. We find that the truncated enzyme catalyses the formation of tyrosyl adenylate with unchanged Kcat and Km values and the crystallographic model must therefore include all the binding and catalytic residues involved in tyrosine activation. However, the truncated enzyme no longer binds tRNATyr or transfers tyrosine to tRNATyr. This indicates that the structural division of TyrTS is equally a functional one: the N-terminal structural domain catalyses tyrosine activation while the disordered C-terminal domain carries major determinants in tRNA binding.